2019
DOI: 10.1039/c9nr02593f
|View full text |Cite
|
Sign up to set email alerts
|

Brilliant blue, green, yellow, and red fluorescent diamond particles: synthesis, characterization, and multiplex imaging demonstrations

Abstract: Rapid thermal annealing of electron irradiated nanoscale type Ib diamond particles facilitates formation of various nitrogen-related fluorescent color centers, providing either red, yellow, green, or blue fluorescence for downstream multiplex imaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…Adámas Nanotechnologies (Raleigh, NC, USA) produced the green FNDs used in the study. The detailed material synthesis, characterization and optical properties are described in Dei Cas et al, 2019 [ 85 ] and Nunn et al, 2019 [ 68 ]. FNDs with green fluorescence emission were produced from synthetic type Ib high-pressure high temperature (HPHT) nanodiamond particles with an initial substitutional nitrogen content of 100 ppm and average particle size of 100 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adámas Nanotechnologies (Raleigh, NC, USA) produced the green FNDs used in the study. The detailed material synthesis, characterization and optical properties are described in Dei Cas et al, 2019 [ 85 ] and Nunn et al, 2019 [ 68 ]. FNDs with green fluorescence emission were produced from synthetic type Ib high-pressure high temperature (HPHT) nanodiamond particles with an initial substitutional nitrogen content of 100 ppm and average particle size of 100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…FNDs are well compatible with multimodal imaging techniques such as stimulated emission depletion microscopy (STED) [ 19 , 50 , 62 , 63 ], two-photon microscopy [ 64 , 65 ], photoacoustic microscopy [ 66 , 67 ], and live-cell fluorescence microscopy [ 19 ]. The notable color centers are those emitting in blue, green, yellow, red, and near-infrared spectral regions [ 68 , 69 , 70 ]. For cell imaging, FNDs are biocompatible, non-toxic, and can be internalized efficiently in the cell via endocytosis [ 47 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…The new effect of RHPHT annealing is to increase the luminescence efficiency in diamonds. It can be useful for some practical applications, for example, generation of scintillators [71] and fluorescent markers [9,[72][73].…”
Section: Photoluminescencementioning
confidence: 99%
“…This remarkable ability to controllably manipulate and read out changes in the electronic state of the NV − center make it a powerful probe for applications spanning from quantum information processing, to biology and applied medical physics. While a number of demonstrations using fluorescent diamond purely as a fluorescent label have been shown [4][5][6], diamond stands out against competing materials in sensing applications where the readout of fluorescence modulation is used to obtain information about the environment surrounding the optical center (e.g., biological sensing [7][8][9][10][11]) and can also be utilized for background-free imaging based on the magnetic modulation of the fluorescent signal [12,13]. While bulk (electronic grade single crystalline plates) diamond containing an engineered array of subsurface NV − centers has been demonstrated to advance quantum computing [14][15][16] and nano-NMR [17][18][19][20] applications, the use of diamond particles as nano-and microscale quantum probes holds the most promise for the future of high-tech particulate diamond applications.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that high-temperature annealing can facilitate the controlled formation of a range of color centers in synthetic (HPHT) diamond particles [5,30], allowing for a greater flexibility for the use of synthetic precursors. This is an important step since, unlike natural diamonds, synthetic diamonds afford more control over critical factors such as nitrogen content and distribution.…”
Section: Introductionmentioning
confidence: 99%